PENGEMBANGAN KOMPETENSI APARATUR MELALUI PENDIDIKAN FORMAL DAN PELATIHAN DI DINAS PEKERJAAN UMUM PROVINSI KALIMANTAN TIMUR - Muhammad Yusran (Jurnal Paradigma (JP), 2017)
The purpose of this study was to describe and analyze the Administrative Competence Development Through Formal Education and Training in the Department of Public Works in East Kalimantan Province. The results showed that the apparatus competence development undertaken by Public Works Department of East Kalimantan Province through Formal Education and various training has managed to bring a better change. The evidence suggests able to increase the competence of the apparatus. Indicated by the increase in personnel who have a Bachelor or Masters level education. In accumulative competence development apparatus made public Works Department of East Kalimantan Province pretty good indication. Less than optimal development of the apparatus due to the limited competence of the budget allocated for the development of personnel competence so that efforts to increase the competence of less than optimal, the limited quality training institutions and diverse commitment to improve the competence of personnel, and the limited authority of the Head of Department of Public Works